Education in Childhood 2021
DOI: 10.5772/intechopen.99103
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Time for Planning, Assessment and Development Connected to Staff Well-Being in Early Childhood Education

Abstract: The planning, assessment and development (PAD) of pedagogy carried out by early childhood education (ECE) teachers is an important quality factor in ECE. In Finland, the working hours reserved for PAD tasks for ECE teachers were increased from 8 to 13% in 2018. The purpose of this study was to investigate ECE teachers’ and centre directors’ perceptions of the impact of increased PAD hours on the well-being of ECE staff. Based on the mixed-methods approach, 325 ECE teachers and 107 ECE centre directors particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…There is also preliminary evidence regarding how more coherent professional requirements have a positive effect on occupational motivation and well-being among ECE teachers. After the national contractual regulation (540/2018) for increased ECE teachers' planning, assessment, and development (PAD) hours was enacted, the change affected ECE teachers positively but other staff negatively (Heikka, Kahila et al, 2021). To enable professional development Journal of Early Childhood Education Research 12(2) 2023, 71-97. https://journal.fi/jecer for the staff with B.Ss.…”
Section: Discussionmentioning
confidence: 99%
“…There is also preliminary evidence regarding how more coherent professional requirements have a positive effect on occupational motivation and well-being among ECE teachers. After the national contractual regulation (540/2018) for increased ECE teachers' planning, assessment, and development (PAD) hours was enacted, the change affected ECE teachers positively but other staff negatively (Heikka, Kahila et al, 2021). To enable professional development Journal of Early Childhood Education Research 12(2) 2023, 71-97. https://journal.fi/jecer for the staff with B.Ss.…”
Section: Discussionmentioning
confidence: 99%
“…According to the respondents, teamwork was influenced by personal chemistry, views of how to act with children (also in Ukkonen-Mikkola et al, 2020), sufficient staff (also in Ranta, 2020), staff structure, education of employees, values (also in Melasalmi & Husu, 2019), and support of the director (also in Ranta, 2020;Ranta & Uusiautti, 2022). Additionally, the appreciation for each team member, profession, and professional expertise was felt to be important for the positive experiences related to teamwork (see Heikka et al, 2021). Some respondents also reported that they do not have enough education to work in teams or that their education does not pay enough attention to working in teams.…”
Section: Discussionmentioning
confidence: 99%
“…In the Finnish ECE, the work is mainly done in multi-professional teams, which can be considered a strength of the Finnish system. However, a multi-professional team may contain tensions that affect the quality of work and the well-being of employees (Heikka et al, 2021;Melasalmi & Husu, 2019;Ranta & Uusiautti, 2022). There is always emotion and tension in the cooperation between employees.…”
Section: Previous Literature On Emotions In Teamworkmentioning
confidence: 99%
“…Teamwork evokes different feelings among employees, and employees may find it challenging to discuss dissenting opinions (Melasalmi, 2018;Ranta et al, in press). However, research shows that team interaction and a culture of open discussion promote the functionality of teamwork (Paakkanen et al, 2021;Ranta & Uusiautti, 2022) and that silence surrounding problems may lead to an increase in teamwork challenges (Heikka, et al, 2021;Melasalmi & Husu, 2019).…”
Section: Introductionmentioning
confidence: 99%